The Promise of Alliance: NATO and the Political Imagination - Thomas, Ian Q.R. (Rowman & Littlefield Publishers, 1997)
The nature and function of the North Atlantic Treaty Organization (NATO) are uncertain now that the alliance has accomplished its primary objective of defending Western Europe from the perceived Soviet threat. Despite uncertainty about NATO's role in the post-Cold War world, its political and military leaders agree that it can continue to play a vital part in enhancing European security and maintaining international stability. This superb analysis explores the evolving functions and future directions of this unique organization, paying particular attention to the political cultures and goals of its member states. The Promise of Alliance is important reading for students and scholars of international relations, foreign affairs, and political theory.